2018
DOI: 10.1038/s41598-018-33594-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of Eucalyptus plantations on soil microbial communities and soil-atmosphere methane and nitrous oxide exchange

Abstract: Soil greenhouse gas (GHG) emissions are a significant environmental problem resulting from microbially-mediated nitrogen (N) and carbon (C) cycling. This study aimed to investigate the impact of Eucalyptus plantations on the structure and function of a soil microbial community, and how resulting alterations may be linked to GHG fluxes. We sampled and monitored two adjacent Eucalyptus plantations—a recently logged site that harbored new seedlings and an adult plantation—and compared them to a site hosting nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 54 publications
2
7
0
1
Order By: Relevance
“…The denitrifying gene markers tracked changes in N 2 O fluxes in some but not all cases, and their poor prediction of N 2 O dynamics may indicate that other microbial N cycling processes were also important (Martins et al, 2015). Increased N 2 O fluxes in the wet season in the field and incubation experiments were accompanied by increasing nirK gene abundances in the soil from all sampling sites.…”
Section: Discussionmentioning
confidence: 95%
“…The denitrifying gene markers tracked changes in N 2 O fluxes in some but not all cases, and their poor prediction of N 2 O dynamics may indicate that other microbial N cycling processes were also important (Martins et al, 2015). Increased N 2 O fluxes in the wet season in the field and incubation experiments were accompanied by increasing nirK gene abundances in the soil from all sampling sites.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to having overall significant effects, these responses were also remarkably universal across studies (Figure 3). Only two studies reported any changes in abundance that were opposite to the summary effect; Firmicutes were reported to decrease in Cuer et al (2018), and Schneider et al (2015) reported a decrease in Actinobacteria and increase in Acidobacteria with conversion (Figure 4).…”
Section: Compositionmentioning
confidence: 97%
“…Conversion from a primary evergreen broadleaf forest to a Eucalyptus urophylla plantation resulted in a decrease in microbial biomass C, urease, invertase, and acid phosphatase (ACP) activities in 5‐year‐old stands, but an increase for 10‐year‐old stands (Zhu et al, 2019). Bacterial richness increased following forest conversion in tropical regions (Lan et al, 2018; Nakayama et al, 2019), but decreased in temperate regions (Cuer et al, 2018; Xia et al, 2015). These mixed results among field studies have led to substantial uncertainty when predicting the consequences of natural forests conversion to plantations.…”
Section: Introductionmentioning
confidence: 99%